PENGARUH LIMBAH DOMESTIK TERHADAP KUALITAS AIR TANAH BEBAS DI KECAMATAN JETIS, KOTA YOGYAKARTA - , ERLAND YOGA NUGRAHA ([Yogyakarta] : Universitas Gadjah Mada, 2013)
This research study about unconfined groundwater quality that affected by domestic waste at Jetis District , Yogyakarta city . Domestic waste contamination to the groundwater using indicators such as ammonia , nitrate , nitrite , BOD , COD , detergents and fecal coliforms bacteria . The purpose of this research is: 1) to determine the quality of groundwater from domestic waste pollution in the District Jetis, 2) to determine spatial diffusion of detergent ingredient , nitrate ( NO3 ) , nitrite ( NO2 ) , ammonia ( NH3 ) , BOD , COD and coli bacteria as an indicator of domestic waste that contaminates groundwater in each class population density in the study area, 3) to determine the influence of domestic waste toward unconfined groundwater quality in the study area. The method used in this research is stratified random sampling method to select wells that belongs to a class of high DHL as an early indicator of groundwater contamination . Another method that is used in addition to purposive random sampling is a systematic method using grid / box measuring 200 m x 200 m on the administration map. Grid method is used for the first time the author did not know the existence of the wells in the study area. Once the existence of wells in the study area are known then stratified random sampling method is used to determine the sample to be studied the physical, chemical and biological parameters based on domestic waste. The analysis shows groundwater in the study area has not been polluted by the physical properties of domestic waste that is still suitable for consumption . For the chemical properties, BOD values in the study area has passed the drinking water quality standard . While COD, ammonia , nitrate , and nitrite has not crossed the line . For the biological properties , groundwater in the study area has largely been contaminated by fecal coliforms bacteria that needs special treatment when used for drinking water. High value of DHL, population density , groundwater flow direction and depth of groundwater in the study area does not always describe the magnitude of groundwater pollution by domestic waste. Unconfined groundwater quality in the study area is largely determined by the sanitary condition of a piping system centralized wastewater treatment ( sewerage system) , septic tanks and communal wastewater treatment .